Determinant Carbon Emission Disclosure with Institutional Ownership as Moderation - Nadia Agnes Melinda; Luh Gede Krisna Dewi (E-Jurnal Akuntansi, 2026)
This study aims to examine the effect of environmental performance and media exposure on carbon emission disclosure and the role of institutional ownership as a moderating variable. Firm size, profitability, and industrial type are operated as control variables. Non-financial companies listed on the Indonesia Stock Exchange for the period 2019-2023 were observed in this study. The sample of this study was obtained through purposive sampling method which resulted in 235 observations. Data analysis using the EViews program with the Moderated Regression Analysis (MRA) method using the Random Effect Model. The results showed that environmental performance has a positive and significant effect on carbon emission disclosure, while media exposure has no effect on carbon emission disclosure. In addition, institutional ownership is not able to strengthen the influence of environmental performance and media exposure on carbon emission disclosure.